The Effect of Macroeconomics and the State Budget on State Sharia Securities in Indonesia - Yusi Gumansari; Nurul Huda (Share: Jurnal Ekonomi dan Keuangan Islam, 2023)
This study aims to investigate the impact of various macroeconomic indicators and the State Budget on State Sharia Securities (SSS) in Indonesia. It employed secondary data from the first to the fourth quarter of 2022 and analyzed using the PLS-SEM (Partial Least Squares - Structural Equation Modeling) method, which allowed for estimating the multiple relationships between dependent and independent constructs. The findings reveal significant direct or indirect effects of macroeconomic indicators, represented by inflation rates, real GDP, benchmark interest rates, and oil commodity prices, had a significant direct or indirect effect on SSS. Furthermore, the State Budget, as reflected by tax revenue and government foreign debt with a remaining time of ≤ 1 year, exhibited a significant positive impact on the volume of SSS issuance and outstanding. It is important to note that macroeconomic indicators were found to have a significant negative effect on the State Budget, highlighting the interplay between these variables. The predictive value of the model employed in this study demonstrates its relevance in elucidating the underlying patterns in the data. These findings have valuable implications for policymakers, providing them with essential insights for the effective management of SSS as a prominent Islamic public financing instrument in Indonesia. They are advised to maintain continuous monitoring of both macroeconomic indicators and the State Budget to identify necessary changes related to the volume of SSS issuance.========================================================================================================ABSTRAK – Pengaruh Indikator Makroekonomi Dan APBN Terhadap SBSN. Penelitian ini bertujuan untuk menganalisis pengaruh indikator makroekonomi dan Anggaran Pendapatan dan Belanja Negara (APBN) terhadap Surat Berharga Syariah Negara (SBSN) di Indonesia. Penelitian menggunakan data sekunder periode triwulan I/2012 sampai dengan triwulan IV/2022. Analisis data dilakukan dengan menggunakan metode PLS-SEM (Partial Leased Square - Structural Equation Modeling) untuk mengestimasi hubungan antar variabel yang bersifat multiple relationship antara konstruk dependen dengan indipenden. Hasil kajian menunjukkan bahwa indikator makroekonomi yang diwakili oleh tingkat inflasi, PDB riil, suku bunga acuan dan harga komoditas minyak memiliki pengaruh signifikan baik langsung maupun tidak langsung terhadap SBSN. Kemudian APBN yang diwakili dengan penerimaan pajak dan utang luar negeri pemerintah yang memiliki jangka waktu sisa £ 1 tahun memiliki pengaruh positif yang signifikan terhadap volume penerbitan/outstanding SBSN. Selanjutnya, indikator makroekonomi diketahui memiliki pengaruh signifikan negatif terhadap APBN. Model yang digunakan dalam penelitian ini memiliki nilai prediktif yang relevan untuk menjelaskan informasi yang ada dalam data penelitian. Implikasi hasil penelitian memberikan masukan bagi pembuat kebijakan dalam mengelola SBSN sebagai salah satu intrumen pembiayaan keuangan publik Islami di Indonesia untuk melakukan pemantauan berkelanjutan atas indikator makroekonomi dan APBN sehingga dapat mengidentifikasi perubahan yang perlu dilakukan terkait dengan volume penerbitan SBSN.